INTERCULTURAL COMPETENCE AS AN IMPORTANT PERSONAL CHARACTERISTIC OF THE FUTURE PRIMARY CLASS TEACHER (Psychology Travelogs, 2024)
The article analyzes the views of foreign and domestic scientists on the problem of the formation of intercultural competence.It is emphasized that intercultural competence should be characteristic of specialists of various professions, but it acquires special importance for representatives of the socionomic field (teachers, psychologists, lawyers, social workers, doctors) because they must be able to interact with representatives of different cultures, each of which has its own language, types of behavior, values, customs and traditions.According to the results of the scientific search, the concept of "intercultural competence of the future primary school teacher" was characterized.The components of the intercultural competence of the future primary school teacher are defined and substantiated.Attention is focused on the psychological features of the development of intercultural competence of future primary school teachers.The forms, methods and techniques that contribute to the development of intercultural competence of future primary school teachers have been specified.Factors affecting the development of intercultural competence of future primary school teachers are revealed.Educational disciplines have been identified that play a key role in the development of intercultural competence of future primary school teachers and provide students with theoretical and practical knowledge that allows them to effectively interact with children of different cultural, ethnic and social groups, as well as take these aspects into account in their pedagogical activities.Diagnostic techniques that assess a person's ability to effectively interact with representatives of different cultures are singled out.The main aspects of the preparation of primary school teachers to work with children of different nationalities have been analyzed, which involves the formation of such knowledge and skills as understanding cultural differences, the ability to adapt the educational process in accordance with the needs of children - representatives of different nationalities, the creation of an inclusive environment, as well as the use of methods, which will contribute to the maintenance of mutual understanding, cooperation and equality among students.
Keywords: competence; intercultural competence; future teachers of primary classes; personal characteristic